Construction and Validation of a Video Coding Tool for an Intervention to Improve Parental Feeding. (29th May 2020) - Samson, Margaret; Amin, Sarah; McCurdy, Karen; Moore, Amy; Tovar, Alison
Abstract: Objectives: Home-based interventions have used video-recorded meals to assess feeding practices, yet no studies have used videos to directly provide feedback on the practices observed. This study describes the development and initial validation of a video coding tool to assess feeding practices observed in video-recorded family meals in order to provide feedback to caregivers. Methods: The tool with operational definitions was developed based on the previous literature and other tools that capture caregiver feeding practices. To assess face validity, a sample of child feeding experts ( n  = 6) reviewed the tool and completed an 8-item online survey. Usability and content were assessed on a scale of 0–100, with 100 representing high usability and importance, respectively. The tool was modified based on expert feedback and used by trained research assistants to code 10 video-recorded family meals. Inter-rater reliability (IRR) was calculated and 3 videos were then randomly selected and coded by each research assistant at two different time points to assess test re-test reliability. Results: Expert ratings of tool usability (81.83 ± 11.67) and content (87.67 ± 13.98) included feedback regarding the need to expand the operational definitions to better code practices, in particular with regards to pressure and encouragement. They also suggested merging practices, such as nutrition education and reasoning, which may be difficult to discern in an observational setting. Average IRR was 86.4% with pressure (75.1%) and encouragement (66.9%) having the lowest rates of agreement between coders. Limited choices (100%) and restriction (95.9%) had the highest rates of agreement. For test re-test reliability, the average agreement between the two timepoints was 80.0%. Conclusions: Following the feedback from experts, the face validity of the developed tool improved, and the inter-rater reliability and test re-test reliability of the tool was acceptable. Future studies should focus on the expansion of operational definitions and training efforts to further improve inter-rater and test re-test reliabilities. Funding Sources: This work was supported by the National Institutes on Health National Heart, Lung and Blood Institute [Tovar/R34HL 140, 229].